Wings of Fire : The Brightest Night - Book 5 Book five, The brightest night - Sutherland, Tui, 1978-; Deutsch, Barry; Swirsky, Rachel; Holmes, Mike (Comic book artist); Laiho, Maarta (New York, NY : Graphix, an imprint of Scholastic, 2021)
"Sunny has always taken the Dragonet Prophecy very seriously. If Pyrrhia's dragons need her, Clay, Tsunami, Glory, and Starflight to end the war, she's ready to try. She even has some good ideas how to do it, if anyone would listen to her. But shattering news from Morrowseer has shaken Sunny's faith in their destiny. Is it possible for anyone to end this terrible war and choose a new SandWing queen? What if everything they've been through was for nothing?"--
Keywords: Dragons -- Comic books, strips, etc; Magic -- Comic books, strips, etc; Good and evil -- Comic books, strips, etc; Prophecy -- Comic books, strips, etc; Identity (Psychology) -- Comic books, strips, etc; Imaginary wars and battles -- Comic books, strips, etc; Quests (Expeditions) -- Comic books, strips, etc; Dragons -- Fiction; Magic -- Fiction; Good and evil -- Fiction; Prophecies -- Fiction; Identity -- Fiction; Imaginary wars and battles -- Fiction; Quests (Expeditions) -- Fiction; Fantasy; Fantasy comics; Comics (Graphic works); Graphic novels